The determination of quercetin in Plectranthus scutellarioides(L.) R.Br. leaves extract and its In SilicoStudy on Histamine H4 Receptor - Moektiwardoyo, Moelyono; Levita, Jutti; Sidiq, Syafrudin Purnama; Ahmad, Khoziah; Mustarichie, Resmi; Subarnas, Anas; ., Supriyatna (Indonesian Journal of Pharmacy, 2011)
Plectranthus  scutellarioides  (L.)  R.Br.,  or  jawer  kotok,  Family  Lamiaceae, grows  widely  in  Indonesia,  and  has  a  long  history  of  therapeutic  usage  in Indonesian traditional jamuto cure various diseases. The brownish purple leaves of  Plecranthus  contain  alkaloids,  saponin,  flavonoids,  tannin,  volatile  oils,  and quercetin  which  has  been  proven  to  exert  antiinflammatory  activity.  In  this research,  a  determination  of  quercetin  in  Plecranthus  leaves  extract  was performed and followed by a study of its interaction with histamine H4 receptor to  understand its  anti-inflammatory  activity.  The  dry  leaves  were  macerated by using  a  mixture  of  methanol  and  water  (1:1)  for  48  hours  and  the  solvent  was evaporated  at  low  temperature  (40-50oC).  Analysis  of  quercetin  in  the  extract was performed by using reversed-phase HPLC method LC-10AT VP (Shimadzu), Atlantis  Hilicsilica  C18  (Waters®)  150  mm  x  4.6  mm,  5  µm  as  stationary  phase and  a  mixture  of  acetonitrile,  phosphoric  acid,  and methanol  (40:50:10),  flow rate 0.8 mL/minute.  In silicostudy of quercetin with histamine H4 receptor was performed by using AutoDock Tools 3.0.5. Histamine H4 receptor (H4R) belongs to  G  protein-coupled  receptors  which  is  involved  in arthritis,  asthma,  and inflammations.  The  3D  structure  model  of  H4R  was  built  by  using  MODELLER 9v7.  Quercetin  contained  in  Plecranthus  leaves  extract  was  0.05  %.  This compound interacted with H4R viahydrogen bond formation with Lys158 (2.006 Å)  and  Glu182  (2.048  Å),  and  van  der  Waals  interaction  with  Trp90,  Leu91, Asp94, Tyr95, Phe168, Thr178, Ser179, Tyr319, Phe344, and Tyr340, therefore Plecranthus  leaves  extract  might  have  a  chance  to  be  used  as  histamine  H4 receptor inhibitor.Key  words  :   histamine  H4  receptor,  in  silico  study,  Plecranthus  leaves,  Plectranthus scutellarioides, quercetin